2019
DOI: 10.1029/2019pa003568
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Intermediate Waters Across the Late Glacial Revealed by Paired Radiocarbon and Clumped Isotope Temperature Records

Abstract: Paired radiocarbon and clumped isotope temperature records from U/Th-dated Desmophyllum dianthus corals in the North Atlantic and Southern Ocean provide unique information about the history of intermediate waters (∼1,500-1,700 m) across the late glacial and deglaciation (∼35-10 ka). These measurements allow for the construction of radiocarbon-temperature crossplots, which help to identify water mass endmembers at different times across the deglaciation. Radiocarbon and temperature values from the late glacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 88 publications
2
13
0
Order By: Relevance
“…The Bonifacie et al, 2017 compilation has been found to be suited for carbonate minerals from -1 to 300 °C; however, the low temperature (T <20 °C) calibration points used in their compilation come from labs that produce "shallow slope" calibrations lines. The Caltech clumped isotope lab consistently produces calibration lines with steeper slopes (Ghosh et al, 2006;Tripati et al, 2010;Thiagarajan et al, 2011;Eagle et al, 2013;Hines et al, 2019). Additionally, the slowest growth inorganic calcite in an inorganic calcite experiment show that  47 values are consistent with the steep slope  47 -temperature calibration of Ghosh et al 2006 (see Figure 6 and 7 in (Levitt et al, 2018)).…”
Section:   47 -Temperature Calibrationsupporting
confidence: 67%
“…The Bonifacie et al, 2017 compilation has been found to be suited for carbonate minerals from -1 to 300 °C; however, the low temperature (T <20 °C) calibration points used in their compilation come from labs that produce "shallow slope" calibrations lines. The Caltech clumped isotope lab consistently produces calibration lines with steeper slopes (Ghosh et al, 2006;Tripati et al, 2010;Thiagarajan et al, 2011;Eagle et al, 2013;Hines et al, 2019). Additionally, the slowest growth inorganic calcite in an inorganic calcite experiment show that  47 values are consistent with the steep slope  47 -temperature calibration of Ghosh et al 2006 (see Figure 6 and 7 in (Levitt et al, 2018)).…”
Section:   47 -Temperature Calibrationsupporting
confidence: 67%
“…However, after the transformation of CDW to AAIW, 14 C-depleted waters that were not completely equilibrated with the atmosphere were possibly exported toward the north and decreased the radiocarbon content of intermediate waters in the Arabian Sea (Bryan et al, 2010). The comparison of our Southern Ocean records and the Drake Passage and Tasman coral records ( Figure S5; Burke & Robinson, 2012;Hines et al, 2019) further highlights the importance of the Indian sector and its role in the deglacial carbon cycle. Both records reach modern-like ε 14 C values before the onset of the YD and do not show any excursion during the second rise in atmospheric CO 2 ( Figure S5).…”
Section: Indian Ocean Ventilation During the Ydmentioning
confidence: 63%
“…Coral dredges that were performed at a similar latitude in the Drake Passage and off Tasmania also recorded upwelling CDW (Burke & Robinson, ; Hines et al, ). Converted to epsilon ε 14 C data (as used by Hines et al, ), Drake Passage data show similar values as recorded by PS69/907‐2, while the Tasman Sea corals that are located further to the north than the Drake Passage and our Kerguelen records show higher glacial values and might be indicative of a reduce influence of Pacific Deep Water (Figure S5; Burke & Robinson, ; Hines et al, ). At the end of the LGM, however, ΔΔ 14 C at 567 m (PS69/912) decreased by ~80‰, Δδ 13 C increased by ~0.3‰, and showed a decoupled trend from the atmosphere.…”
Section: Discussionmentioning
confidence: 94%
“…(b) CO 2 compilation record (Bereiter et al, 2015). (c) B-Atmosphere age reconstructed from cold-water corals: Azores Front Corals, Mauritania, and Angola (this study), as well as equatorial Atlantic (Chen et al, 2015(Chen et al, , 2020, New England Seamounts in 1,100-1,400 m depth (NESM; Eltgroth et al, 2006;Hines et al, 2019;Robinson et al, 2005;Thiagarajan et al, 2014), Tasmania (Hines et al, 2015), southwest Australia (Trotter et al, 2022) and Drake Passage (DP, Burke & Robinson, 2012;Chen et al, 2015;Li et al, 2020). Note: All B atm ages have been recalculated using IntCal20 and SHCal20 (Hogg et al, 2020;Reimer et al, 2020).…”
Section: North Atlantic Ventilation During the Lgmmentioning
confidence: 96%
“…The CWCs off Mauritania are located near the Cap Verde Frontal Zone, while those off Angola are situated near the Angola-Benguela-Front. The Benguela Current carries water from the Antarctic Circumpolar Current and Agulhas Current, while the Angola Current flows southward.Our observations are compared to previously published CWC results (white stars) from the New England Seamount(Adkins et al, 1998;Eltgroth et al, 2006;Hines et al, 2019;Robinson et al, 2005;Thiagarajan et al, 2014), equatorial Atlantic(Chen et al, 2015(Chen et al, , 2020, Drake Passage(Burke & Robinson, 2012;Chen et al, 2015;Li et al, 2020), southwest Australia(Trotter et al, 2022) and Tasmania(Hines et al, 2015). (b) Hydrography around sample locations.…”
mentioning
confidence: 96%